City planning : problems and prospects - Yadav, C.S. (ed.) (New Delhi, 1987)
City Planning : Problems and Prospects is an informative, useful, readily applicable reference book planning, programming, on designing and constructing the built up environment. It introduces research scholars in the fields directly concerned with city planning to the scope, subject matter, challenges and opportunities of compre hensive city planning theory. These fields mainly include urban and regional planning, urban and regional studies, public administr ation system and papers presented civil engineering. The here represent compre hensive planning norms applicable to the present day situation and for the immediate future.
Keywords: Urbanisation